Conformational plasticity of the ULK3 kinase domain. Issue 14 (30th July 2021) - Mathea, Sebastian; Salah, Eidarus; Tallant, Cynthia; Chatterjee, Deep; Berger, Benedict-Tilman; Konietzny, Rebecca; Müller, Susanne; Kessler, Benedikt M.; Knapp, Stefan
Abstract : The human protein kinase ULK3 regulates the timing of membrane abscission, thus being involved in exosome budding and cytokinesis. Herein, we present the first high-resolution structures of the ULK3 kinase domain. Its unique features are explored against the background of other ULK kinases. An inhibitor fingerprint indicates that ULK3 is highly druggable and capable of adopting a wide range of conformations. In accordance with this, we describe a conformational switch between the active and an inactive ULK3 conformation, controlled by the properties of the attached small-molecule binder. Finally, we discuss a potential substrate-recognition mechanism of the full-length ULK3 protein.